PERKEMBANGAN PENELITIAN LITERASI SAINS DALAM PEMBELAJARAN FISIKA DI INDONESIA - Nurhasanah Nurhasanah; Jumadi Jumadi; Luh Devi Herliandry; Melta Zahra; Maria Enjelina Suban (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
THE DEVELOPMENT OF SCIENTIFIC LITERACY RESEARCH IN PHYSICS LEARNING IN INDONESIAAbstractScientific literacy is one topic that is starting to get much attention in the academic field. Mastering the ability of scientific literacy is essential for everyone to solve problems. Scientific literacy in physics is very important for life in the era of science and technology. This study aims to provide an overview of research related to scientific literacy in learning physics in Indonesia. This study is to determine the distribution and description of scientific literacy research that has been done so that it is expected to provide direction in conducting further research, improvement, and policy. This research used a descriptive content analysis study method. The instrument used the adopted Paper Classification Form or PCF by Kizilaslan et al. Analysis was carried out on 59 articles relating to the scientific literacy in physics published in 2012-2019. Scientific literacy research in physics in Indonesia continues to increase until its peak in 2018, dominated by topics research in media development, teaching materials, or other learning components that aim to develop student scientific literacy. High school students become a sample that is often used in research, with most using a sample size of 51-100. Types of quantitative research methods and test instruments become more dominant than others. The definition of scientific literacy that is widely used in physics education research in Indonesia is the definition of scientific literacy by PISA. AbstrakLiterasi sains merupakan salah satu topik yang mulai banyak mendapat perhatian dalam bidang akademik. Hal ini dikarenakan penguasaan kemampuan literasi sains yang penting bagi semua orang untuk menyelesaikan masalah. Literasi sains pada fisika sangat penting untuk kehidupan di era sains dan teknologi. Tujuan dari penelitian ini untuk memberikan tinjauan umum terkait penelitian literasi sains dalam pembelajaran fisika di Indonesia. Hal ini untuk mengetahui distribusi dan deskripsi penelitian literasi sains yang telah dilakukan, sehingga diharapkan dapat memberi arahan dalam melakukan penelitian, perbaikan maupun kebijakan lebih lanjut. Penelitian ini menggunakan metode descriptive content analysis study. Instrumen yang digunakan mengadopsi Paper Classification Form atau PCF oleh Kizilaslan et al. Analisis dilakukan terhadap 59 artikel berkaitan dengan literasi sains fisika yang dipublikasikan dalam rentang 2012-2019. Penelitian literasi sains fisika di Indonesia terus mengalami peningkatan hingga puncaknya pada tahun 2018, didominasi oleh topik penelitian pengembangan media, bahan ajar, atau komponen pembelajaran lainnya yang bertujuan untuk mengembangkan literasi sains siswa. Siswa SMA menjadi sampel yang sering digunakan dalam penelitian, dengan sebagian besar menggunakan ukuran sampel 51–100. Jenis metode penelitian quantitative dan instrument tes mendominasi dibandingkan lainnya. Definisi literasi sains yang banyak digunakan dalam penelitian literasi sains fisika di Indonesia yakni definisi literasi sains menurut PISA.